Raising and educating a deaf child : a comprehensive guide to the choices, controversies, and decisions faced by parents and educators - Marschark, Marc (Oxford University Press, 2007)
Preface. Acknowledgments. Foreword. 1. A Deaf Child in the Family. 2. Practical Aspects of Deafness. 3. Communicating with Deaf Children. 4. Early Interactions: The Roots of Childhood. 5. Language Development. 6. Going to School. 7. Learning to Read and Write. 8. Intelligence, Achievement, and Creativity. 9. Deaf Children to Deaf Adults. 10. Where Do We Go from Here?. Appendices.